Elastisitas Penawaran Daging Ayam Broiler di Provinsi Jawa Tengah - Nurdayati, Nurdayati; Nurtini, Sudi; Masyhuri, Masyhuri; Widiati, Rini (2011)
The purpose of this research are (1) Determine the factors that affect the production (supply) of broiler meat. (2) Measuring the elasticity of supply of broiler meat. The basic method used in this research is descriptive method. This study uses time series data from 1999 till 2009, which includes. namely the price of broiler meat, broiler feed price, the price of DOC and broiler meat production in Central Java Province. The model of analysis used to identify several factors that affect the supply of broiler meat and elasticity used multiple regression analysis model Cobb-Douglas function. According to analysis it was shown that, several factors that affect the supply of broiler meat is the price of broiler meat itself and the price of feed, with a regression coefficient of 0.462 for the price of broiler meat are the regression coefficients of input prices - 0.978. Price elasticity of supply of broiler meat have positive signs and are in elastic (e <1). In elastic properties is a change in broiler meat production is less than the change in price or in case of price changes result in big changes to the production of broiler meat.